The Effects of Subordinated Bonds Issued and the Bank Binancial Performance Towards the Stock Trading Volume Activity - Adithia Anggraeni (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2020)
Abstract. According to IDX statistical data of year 2017 the market capitalization of finance sector stock was dominated by the stock of the banking subsector up to 91,87% and the banking subsector has dominated 38,52 % of the corporate bond market in Indonesia. This research aimed to 1) analyzing the financial performance of bond issued bank listed in the IDX from 2013 to 2017, 2) analyzing the effects of the bank subordinate bond issuance towards the stock trading volume activity, 3) analyzing the finance performance of bond issued bank listed in the IDX from 2013 to 2017 towards the stock trading volume activity. This research used the event study method, which implemented the descriptive and the quantitative approaches. The populations in this study were bank companies listed on the Indonesia Stock Exchange or IDX that issued bonds, with the datas from 16 banks as the samples. The hypothesis was analyzed using the multiple linear regression analysis to determine the effects of the bond issuance events and financial performance towards the stock trading volume activity. This research showed that bond issued bank listed in the IDX had a good financial performance from 2013 to 2017. Based on the results of partial regression, the announcement of issuance of corporate bonds, dividends per share, CAR and NIM had a significant influence on stock trading volume activity and the form of influence was positive. NPL and DER had significant effects on stock trading volume activity and the forms of influence were negative.